Aliance of groups 4 and 14 organometallic compounds - Bareš, Josef (Univerzita Pardubice, 2008)
The reactivity of metallocenes and its derivates with stannylenes and plumbylenes stabilized by C,N chelating ligand is described in this work.
Keywords: organokovové sloučeniny; C,N chelátující ligand